2012
DOI: 10.2460/javma.240.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Development of a diagnostic diagram for rapid field assessment of acidosis severity in diarrheic calves

Abstract: Use of the diagnostic diagram may aid differentiation between severe and nonsevere acidosis patterns as determined on the basis of clinical signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
3
6
1
4
Order By: Relevance
“…In accordance with the rule of electric inertness of systemic fluids, the potassium ions shift in an opposite direction (from a cell to extracellular fluid), thus causing an increase in their plasma concentration (Constable and Grunberg 2013). Metabolic acidosis observed in our study might have developed due to the reported loss of fluid and electrolytes in diarrhea (Bellino et al 2012). Furthermore, metabolic acidosis accompanying inflammation, sepsis, shock, and hypoxia is known to deteriorate the coagulation profile (Bick 1996).…”
Section: Discussionmentioning
confidence: 59%
“…In accordance with the rule of electric inertness of systemic fluids, the potassium ions shift in an opposite direction (from a cell to extracellular fluid), thus causing an increase in their plasma concentration (Constable and Grunberg 2013). Metabolic acidosis observed in our study might have developed due to the reported loss of fluid and electrolytes in diarrhea (Bellino et al 2012). Furthermore, metabolic acidosis accompanying inflammation, sepsis, shock, and hypoxia is known to deteriorate the coagulation profile (Bick 1996).…”
Section: Discussionmentioning
confidence: 59%
“…Assessment of the degree of metabolic acidosis on the basis of clinical signs has been investigated by several authors . A calf's demeanor is influenced by the severity of metabolic acidosis, hypothermia and degree of dehydration.…”
mentioning
confidence: 99%
“…However, decreasing levels of these parameters were similar for all concentrate starter composition. Normal ranges for pH (7.31-7.49), PCO2 (46-56mmHg), HCO3 (22-30mEq/L) and BEecf (3-7mmol/L) are well established by the literature (Adams et al 1991, Nagy et al 2006, Do Rego Leal et al 2008, Bellino et al 2012. By analyzing the acid-base imbalance, the disorder may be classified in metabolic or respiratory alkalosis or acidosis.…”
Section: Discussionmentioning
confidence: 96%
“…According to the literature (Nakagawa et al 2007, Bellino et al 2012, calves that have BEecf values from -3 to 7mmol/L are considered normal, lower than -10mmol/L are in metabolic acidosis and lower than -6mmol/L are in severe acidosis. Calves presented values higher than the normal range, suggesting that even at the third day of diarrhea calves were not in acidosis.…”
Section: Discussionmentioning
confidence: 99%